KEWENANGAN PT. PELINDO IV TARAKAN TERHADAP HAK ATAS TANAH DAERAH LINGKUNGAN KERJA PELABUHAN - Endy Kurniawan (JURNAL AKTA YUDISIA, 2019)
Abstract The title of the research is to " LAW REVIEW THE LAND ENVIRONMENT WORKING OF PORT AREAS (DLKr) PT. PELINDO IV OF TARAKAN. The purpose of this research is to analyze the authority of PT PELINDO IV Tarakan as holders of land rights in the form of Rights Management (HPL) the land environment working of port areas. In addition, the study also to analyze the land of rights can be given to the people on ) the land environment working of port areas or coastal region. This Research to use normative legal method to study with the type of normative juridical. As for the approach used in this study is the statute approach and conceptual approach. Sources of legal materials used are primary, secondary and tertiary legal material. Legal materials collection techniques used this study to collect and analyze the Regulation in relating to the legal issues raised, as well as collecting the conceptual framework and legal theory to be the basis of analyzing the legal issues studied. PT. PELINDO IV of Tarakan has the authority to the land environment working of port areas with Right to used (HPL) contained in the Joint Decree of the Minister of Home Affair and Minister of Transportation Number 31 of 1992 K.M Number 9 of 1992 concerning frontier Work Environment Ports. In the fourth dictum of the Joint Decree of the Minister of Home Affair and Minister of Transportation, PT. PELINDO IV of Tarakan required to complete the land registration process in the Land Office in accordance with applicable regulations. Until now PT. Pelindo IV Tarakan not enroll all of the land which they are entitled and limitations affect the authority of PT. Pelindo IV Tarakan on the overall the land environment working of port areas. Keynote : Land Law, HPL, Law Review